“You’re either with us, or you are with the terrorists” – Juxtaposed Ideologies in the War on Terror (FORUM: University of Edinburgh Postgraduate Journal of Culture & the Arts, 2016)
A recent British government policy document has attempted to tackle the various guises of extremism by outlining definitions and proposed solutions for a structural approach to the threat of terror. In doing so, the command paper characterises the relationship between Britain and Islamic terrorists as one of an ideological conflict playing out between Western powers and Muslim fundamentalists. In exaggerating the apparent polarisation necessary for an ideological conflict, I will demonstrate how the text locks us into certain narratives that filter out historical contexts in favour of a binary rhetoric aimed at furthering conflicts based on ideology as natural conclusions, rather than the constructions and manipulations of policy.